Styrylpyridinium Derivatives as New Potent Antifungal Drugs and Fluorescence Probes - Vaitkienė, Simona; Daugelavičius, Rimantas; Sychrová, Hana; Kodedová, Marie (Frontiers in Microbiology, 2020)
The incidence of Candida glabrata infections increases every year due to its higher resistance to commonly used antifungal drugs. We characterized the antifungal mechanism of action of eight new styrylpyridinium derivatives, with various N-alkyl chains (-C6H13, -C8H17, -C10H21, -C12H25) and different substituents, on C. glabrata strains differing in their drug resistance due to the presence or absence of two major drug-efflux pumps. We found that the tested styrylpyridinium compounds affected the growth of C. glabrata cells in a compound- and strain-dependent manner, and apparently they were substrates of CgCdr1 and CgCdr2 pumps. Further, we determined the impact of the tested compounds on plasma membrane integrity. The ability to cause damage to a plasma membrane depended on the compound, its concentration and the presence of efflux pumps, and corresponded well with the results of growth and survival tests. We also tested possible synergism with three types of known antifungal drugs. Though we did not observe any synergism with azole drugs, styrylpyridinium compounds 5 and 6 together with FK506 demonstrated excellent antifungal properties, whereas compounds 2, 3, 5 and 6 exhibited a significant synergistic effect in combination with terbinafine. Based on our results, derivatives 2 and 6 turned out to be the most promising antifungal drugs. Moreover, compound 6 was not only able to effectively permeabilize the yeast plasma membrane, but also exhibited significant synergism with FK506 and terbinafine. Finally, we also characterized the spectroscopic properties of the tested styrylpyridinium compounds. We measured their absorption and fluorescence spectra, determined their localization in yeast cells and found that their fluorescence characteristics differ from the properties of current commercial vacuolar styrylpyridinium markers and allow multi-color staining. Compounds 1, 3, 7 and 8 were able to accumulate in plasma and vacuolar membranes, and compounds 2, 5 and 6 stained the whole interior of dead cells. In summary, of the eight tested compounds, compound 6 is the most promising antifungal drug, compound 8, due to its minimal toxicity, is the best candidate for a new vacuolar-membrane probe or new benchmark substrate of C. glabrata Cdr pumps and derivative 5 for a new vital dye.